The Determinants of Manufacturing Firms' Transfer Pricing Decisions in Indonesia - Badingatus Solikhah; Deni Dwi Aryani; Anna Kania Widiatami (Jurnal Keuangan dan Perbankan, 2021)
The purpose of this study is to analyze the influence of tunneling incentives, corporate governance mechanisms, foreign operations, bonus mechanisms, and debt covenants toward transfer pricing. This study compares two proxies for transfer pricing variables: Related Party Transaction Asset and Liability (RPTAL) and Transfer Pricing Intensity (TPI). Manufacturing companies that have transactions with foreign related parties are employed in this study. The researchers purposively selected the Panel data from 24 companies in the period 2014 - 2018. There were 120 units analyzed using panel data regression. The research shows that transfer pricing practice via asset and liability transactions (RPTAL) and related parties receivables transaction is relatively high. The difference in the scope of measurement with the RPTAL and TPI causes differences n the study results in model 1 and model 2. Model 1 showed tunneling incentives, foreign operations, and debt covenants proved to have a significant positive effect. In model 2, it is found there is a positive association between tunneling incentives and transfer pricing.DOI: https://doi.org/10.26905/jkdp.v25i1.5127